The laughing corpse eaudiobook - Hamilton, Laurell K. (Anita Blake, Vampire Hunter, 2009)
The early Anita Blake novels find new life in trade paperback-as perfect collectibles for long-time fans or as great ways for new readers to sink their teeth into the series. In The Laughing Corpse , a creature from beyond the grave is tearing a swath of murder through St. Louis. And Anita will learn that there are some secrets better left buried-and some people better off dead...